Standards of Care in Diabetes-2025 - P.S. Shankar; M V Jali (RGUHS Journal of Medical Sciences)
Physicians worldwide wait each year for the publication of the American Diabetes Association ADA Standards of Care in Diabetes as it initiates significant transformation in the management of diabetes. The guidelines for 2025 have been published on 9th December 2024. These guidelines have been regarded as an important resource for evidence-based clinical practice. The guidelines significantly influence the diagnosis treatment and prevention of diabetes across diverse groups of individuals worldwide. By integrating the latest advancements in research therapeutics and technology the ADA has provided a succinct comprehensive roadmap to the management of diabetic patients.